Development of mobile intelligent poultry feed dispensing system (2010)
"Feeding in poultry farming in most developing countries, like Nigeria, is still manually carried out as high level of human involvement is required. This places an exorbitant cost of production on the farmer and reduces the expected return from investment. Besides, human intervention to poultry feeding is limited to fatigue, negligence, unfavourable weather conditions, and improper administration of feeds. In this paper, we present a microcontroller based poultry feed dispensing system.The mobile intelligent system is capable of moving forward, turn left, right and has the ability to detect and avoid obstruction. The developed model shows how mechanical transmission systems in machine can imbibe human intelligence of poultry attendants with corresponding increases in cost-benefits and high profits yield from a reduced labour force in poultry farming. "